Multiple cutaneous reticulohistiocytoma - Karishma D Hemmady; Shylaja S Someshwar; Hemangi R Jerajani (Wolters Kluwer Medknow Publications, 2016)
Multicentric reticulohistiocytosis is a rare non-Langerhans cell histiocytosis characterized in its full form by severe destructive arthritis, cutaneous nodules, and systemic manifestations. Cutaneous lesions may precede, accompany, or more commonly develop later than other features in this disease. We describe a case of multiple cutaneous reticulohistiocytoma without any systemic associations after thorough investigations.